Validity and reliability of Malay breast cancer awareness scale for male-to-female transgender - Draman, Samsul; Md Zin, Hezlin; Shalihin, Mohd Shaiful Ehsan; Mohd Rus, Razman (Faculty of Medicine Universiti Kebangsaan Malaysia, 2022)
The breast cancer risk among female transgender for those using hormonal therapy is emerging. However, most of them also engaged in breast implant procedures resembling female sexual characteristics and satisfaction without realizing the risk of cancer. Thus, breast cancer risk assessment of female transgender in Malaysia should be further evaluated. This study aims to develop and validate an assessment tool in the Malay version to measure breast cancer awareness among female transgender in Malaysia. A cross-sectional study with a purposive sampling method was conducted among 300 respondents in Pahang, Kedah, and Kelantan. The minimum number of respondents required was 300 persons based on the Nunnally method, with an item ratio of 1: 10. All the subjects were given questionnaires on sociodemographic data and breast cancer-related items, consisting of five domains; knowledge of symptoms and clinical features, breast cancer risk factors, breast screening programs, barriers in seeking medical help, and lastly, the confidence, skills and behaviour concerning breast self-examination. Each domain consists of five to seven items. All the responses are recorded as ‘Yes,’ ‘No,’ or ‘Not Sure’ responses. Reliability was determined using Cronbach’s alpha for internal consistency, while construct validity was assessed using exploratory factor analysis. The reliability of this 28 items questionnaire was 0.864 with five meaningful domains as highlighted. This Malay Breast Cancer Awareness Scale is a convenient self-assessment method, inexpensive and understandable which highlights common issues faced male to female transgender with targeted domains. In conclusion, this scale is valid and reliable by achievable internal consistency value of 0.864.